Long-term functional rescue of trauma-induced vision loss by a novel, small molecule TrkB modulator - Shweta Modgil; Christopher L. Walker; Micah A. Chrenek; Hans E. Grossniklaus; Frank E. McDonald; P. Michael Iuvone (PLoS ONE, 2025)
Brain-derived neurotrophic factor (BDNF) signaling through the tropomyosin-related kinase B (TrkB) receptor promotes neuronal growth and survival following an injury. However, its short half-life and pleiotropic effects limit the clinical use of BDNF as a therapy in neurodegenerative disorders. Identification of novel and selective TrkB activators may ameliorate the damage caused to retinal neurons during eye-related injuries and may reduce adverse visual outcomes associated with visual trauma. We previously described a small molecule, N-[2-(5-hydroxy-1H-indol-3-yl) ethyl]-2-oxopiperidine-3-carboxamide (HIOC), that activates TrkB and reduces the decline in visual function in a mouse model of ocular trauma. Using the lead optimization approach, we subsequently synthesized a fluoropyridine analog of HIOC, 2-fluoro-N-(2-(5-hydroxy-1H-indol-3-yl) ethyl) nicotinamide (HIFN), which also successfully activates TrkB. HIFN is a more potent TrkB modulator than the parent compound, HIOC. Further, treatment with HIFN demonstrated neuroprotection in an animal model of overpressure ocular blast injury, ameliorating blast-related visual functional decline. Mice treated with HIFN had better visual acuity, contrast sensitivity, and retinal function supported by enhanced survival of retinal ganglion cells compared to vehicle-treated animals. Moreover, HIFN exhibited better protective effects than HIOC. The therapeutic effects of HIFN were attributed to TrkB activation, as blocking the receptor with a selective receptor antagonist (ANA-12) abrogated the neuroprotection. Together, our results identify HIFN, a novel TrkB receptor modulator, as a strategy for decreasing retinal degeneration and progressive vision loss associated with traumatic ocular injury. In addition, this compound may have broader applications in treating other diseases with altered TrkB activity.